Utilization of Artificial Intelligence to Enhance the Quality of Islamic Education Learning at Islamic Boarding School Hatyai, Thailand - Setiawan, Hasrian Rudi; Limbong, Isman Efendi; Hasan, Ibrahim; Prayogi, Azmi; Chakireen, Chakireen (Yayasan Rahmat Islamiyah, 2025)
The rapid advancement of Artificial Intelligence (AI) technology has significantly transformed various fields, including education. This study aims to optimize the utilization of AI to enhance the quality of Islamic education learning at Islamic Boarding School Hatyai, Thailand. The methods employed in this community service initiative include training teachers to use AI applications for designing more interactive and adaptive teaching materials, as well as implementing AI for personalized student learning experiences. The expected outcomes of this initiative are improved learning effectiveness, higher student engagement, and enhanced teacher capabilities in utilizing AI technology optimally. Therefore, AI implementation is expected to provide innovative solutions for improving the quality of Islamic education in technology-based boarding schools.